Predictors of Sensitivity in Mothers of 8-Month-Old Infants - Alvarenga, Patricia; Dazzani, Maria Virginia Machado; Lordelo, Eulina da Rocha; Alfaya, Cristiane Ajnamei dos Santos; Piccinini, Cesar Augusto (Paidéia (Ribeirão Preto), 2013)
This longitudinal study investigated the impact of maternal mental health, including postpartum depression, and of maternal-fetal attachment, on maternal sensitivity when babies were eight months old. The study included 38 mother-infant dyads. The women answered the SRQ-20 and the Maternal-Fetal Attachment Scale in the third trimester of pregnancy, and the BDI, for evaluation of postpartum depression in the first month following birth. Maternal sensitivity was examined through an observation of mother-child interaction when babies were eight months old. The multiple regression model considering the three factors explained 18.6% of the variance in sensitivity, and only maternal-fetal attachment was a significant predictor. The results indicate the importance of interventions to promote the bond of pregnant women with their babies, which may even minimize possible harmful effects of postpartum depression on mother-child interaction.